LncRNAs could play a vital role in osteosarcoma treatment: Inhibiting osteosarcoma progression and improving chemotherapy resistance - Xiaotong, Shi; Xiao, Li; Shiyu, Liao; Zhiguo, Bi; Chunyang, Feng; Jianguo, Liu (Frontiers in Genetics, 2023)
Osteosarcoma (OS) is one of the most common primary solid malignant tumors in orthopedics, and its main clinical treatments are surgery and chemotherapy. However, a wide surgical resection range, functional reconstruction of postoperative limbs, and chemotherapy resistance remain as challenges for patients and orthopedists. To address these problems, the discovery of new effective conservative treatments is important. Long non-coding RNAs (lncRNAs) are RNAs longer than 200 nucleotides in length that do not encode proteins. Researchers have recently found that long non-coding RNAs are closely associated with the development of OS, indicating their potentially vital role in new treatment methods for OS. This review presents new findings regarding the association of lncRNAs with OS and summarizes potential clinical applications of OS with lncRNAs, including the downregulation of oncogenic lncRNAs, upregulation of tumor suppressive lncRNAs, and lncRNAs-based treatment to improve chemotherapy resistance. We hope these potential methods will be translated into clinical applications and greatly reduce patient suffering.